Life Cycle Assessment of Environmentally Friendly Solutions for the Construction of Unpaved Rural Roads - Mattia Di Sessa; Pier Paolo Riviera; Lucia Tsantilis; Leonardo Urbano; Orazio Baglieri; Ezio Santagata (Infrastructures, 2023)
In recent decades, the international community has recognized the detrimental impact of the construction industry on the environment. In recent years, the use of recycled aggregates has attracted increasing interest as a sustainable and cost-effective solution for the construction and maintenance of road pavements. The life cycle assessment (LCA) represents a valuable methodology for evaluating the environmental sustainability of technologies involving the use of such materials. This study deals with the LCA of alternative solutions for the construction and maintenance of unpaved rural roads. Different scenarios using recycled materials, such as reclaimed asphalt and mineral sludge, are analyzed and compared to a reference solution that employs only virgin aggregates. The environmental sustainability of the proposed alternatives is assessed by considering the global warming potential (GWP), energy requirements, and water consumption. The LCA analysis is performed using SimaPro software (version 9.1.1.7). The obtained results demonstrate that solutions involving the use of recycled materials represent a more sustainable and environmentally friendly option. In particular, a significant reduction in water depletion was found for the alternative scenarios, with savings between 56% and 99%. For GWP and energy, the total savings ranged from approximately 20% to 40%.